PELATIHAN PEMBUATAN DAN E-MARKETING MASKER RAJUT DHAKNIT DI DESA KARANGANYAR PONCOKUSUMO - Fitria Khasanah; Dhania Eka Widyaningrum; Lia Farah Camelia Firdausiah; Yunita Oktavia Wulandari; Ruvita Iffahtur Pertiwi; Cynthia Tri Octaviani (STKIP PGRI SITUBONDO, 2026)
After the Covid 19 pandemic, many family economies have fallen, especially the lower middle class. Most of the residents of Karanganyar Poncokusumo Village work as farmers, traders and laborers who have been affected by the layoffs so that their income has decreased. Housewives are required to help the family economy. Some housewives have sewing skills and make beads on sandals, shoes and bags. As a result of the pandemic, market demand has decreased, the craftsmen have not returned to work. There is potential and team members have knitting skills, so the team provides training in making and e-marketing knitted masks. The need for masks during a pandemic has increased in accordance with government recommendations to use masks when doing activities outside the home and staying fashionable. Knitting mask training and e-marketing activities were carried out in Karanganyar Village for 7 meetings with 2 activities namely training on making knit masks and connectors, as well as e-marketing or online sales. The training participants totaled 15 housewives. For E-marketing the team socializes Facebook and Instagram social media as well as the Shopee Market Place. The results of the training participants produced 25 connectors and 20 knitted masks of various shapes, wallets, bags, and also barbie doll clothes. Currently the participants are learning to make a bouquet of flowers from knitting. In addition, a business group of women was formed in Karanganyar Poncokusumo village with knitting as the basis.